Narrative inquiry study: Teacher’s and students’ experiences on using vocabulary self-collection strategy - Barata, Miftha Nugi; Hapsari, Christianti Tri (ELT Forum: Journal of English Language Teaching, 2025)
The vocabulary self-collection strategy, considered effective in enriching students' vocabulary and motivating them to continue learning, is a topic worthy of research. Most previous research findings on the effectiveness of this strategy were obtained through pre-tests and post-tests administered by researchers to respondents. The primary focus of the current research was on the experiences of the teacher and students regarding the use of the Vocabulary Self-Collection Strategy, which is considered a practical approach for improving students' vocabulary and motivation. This also creates a research gap between this study and several other studies. Narrative inquiry is the approach used by the researchers in this study to obtain more in-depth information from respondents. Interviews conducted by the researchers with an English teacher and several fourth-grade students at an elementary school in Ungaran Timur, as well as narratives written by respondents, served as the two main instruments in this study. Both instruments presented experiences in the form of positive impacts and obstacles experienced by students in using this strategy. Thus, the implementation of this strategy not only has a positive effect but also gives rise to several obstacles encountered by teachers and students.